2014
DOI: 10.1111/clr.12433
|View full text |Cite
|
Sign up to set email alerts
|

Bone remodeling at implants with different configurations and placed immediately at different depth into extraction sockets. Experimental study in dogs

Abstract: Subcrestal immediate implant positioning may lead to a relatively reduced CB resorption and increased BIC. Implants macrodesign with crestal microrings may enhance BIC in post-extraction implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 50 publications
3
12
0
Order By: Relevance
“…Another limitation is related to the location of the implant-abutment interface in relation to the bone crest [4]. Some studies have reported that the use of internal connection at the subcrestal level is better to preserve the bone tissue [59][60][61]. However, only two studies reported on implants placed subcrestally (0.5 mm [36] and 1 mm [44]), although in both external and internal connections.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is related to the location of the implant-abutment interface in relation to the bone crest [4]. Some studies have reported that the use of internal connection at the subcrestal level is better to preserve the bone tissue [59][60][61]. However, only two studies reported on implants placed subcrestally (0.5 mm [36] and 1 mm [44]), although in both external and internal connections.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale of installing the implant anchored in the palatal wall and 4 mm below the buccal gingival margin is to create an adequate emergence profile from the narrow implant platform, increasing the formation/reconstruction of the buccal bone wall to obtain stable results of the hard and soft tissues in the long term [19, 23, 24]. Graft resorption in the horizontal aspect can be equalized by the use of a thick connective tissue graft [25].…”
Section: Discussionmentioning
confidence: 99%
“…Different loading protocols were evaluated, because mechanical loading influences bone remodeling [ 11 ], and this variable was not considered in the studies from Hermann et al [ 2 ], Todescan et al [ 3 ], Negri et al [ 7 ], Boquete-Castro et al [ 8 ], and Calvo-Guirado et al [ 9 , 10 ], in which prostheses were not installed.…”
Section: Discussionmentioning
confidence: 99%
“…On its turn, Calvo-Guirado et al [ 10 ] evaluated different implant geometry (external hexagon, internal hexagon, and internal conical connection). Implants inserted 2 mm subcrestally resulted in 47.33 ± 5.23%, 48.38 ± 11.63%, and 54.88 ± 11.73.%, while those inserted at crestal level resulted in 42.52 ± 8.67%, 35.19 ± 18.12%, and 47.46 ± 11.50%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation